Public Interest: A Critical Analysis of Its Practical Application in Islamic Shari’ah and Contemporary Laws in the Modern Context - (Dr.) Zainab Amin (Correspondence author),; (Dr.) Nazia Irfan,; (Dr). Salma Anjum,; (Dr.) Samina Begum, (Al-Qanṭara, 2024)
This title suggests a comprehensive examination of how the concept of public interest is implemented within both Islamic Sharia law and modern legal systems. It implies a comparative study that evaluates the relevance, challenges, and implications of applying public interest principles across these two legal frameworks, particularly in today's socio-political environment. Concept and Definition: Public interest (Maslaha in Islamic terms) is a fundamental principle aimed at ensuring the welfare and well-being of the community. In Islamic Sharia, it is rooted in the objectives of Sharia (Maqasid al-Sharia) and derived from primary sources such as the Quran, Hadith, Ijma (consensus), and Qiyas (analogical reasoning). Contemporary legal systems, on the other hand, embed public interest within constitutions, statutory laws, and judicial precedents, often balancing it against individual rights and freedoms. Categories and Scope: Islamic Sharia classifies public interest into three categories: necessities (Daruriyyat), needs (Hajiyyat), and embellishments (Tahsiniyyat). These categories ensure the protection of essential elements such as life, religion, intellect, lineage, and property. In contemporary law, public interest encompasses aspects like public health, safety, welfare, and morals, and is interpreted based on societal values and norms. Principles and Application: In Islamic Sharia, principles like Istislah (public welfare) and Ijtihad (independent reasoning) are used to derive rulings that serve the common good, particularly when explicit texts are absent. Contemporary legal systems rely on legislation, policy-making, and judicial review to uphold public interest, ensuring laws and policies serve the broader community while respecting individual rights. Challenges: Both Islamic Sharia and contemporary law face challenges in applying the concept of public interest. In Sharia, divergent interpretations among scholars, the need to balance tradition with modernity, and potential political manipulation can complicate the impartial application of public interest. Contemporary legal systems grapple with the subjectivity of public interest, the need to balance it with individual rights, and addressing transnational issues like climate change and pandemics. Case Studies: Examples in Islamic Sharia include fatwas supporting vaccination and public health measures during pandemics and the implementation of Zakat (charity) systems to alleviate poverty. In contemporary law, public health laws mandating vaccinations and quarantine during health crises and environmental protection legislation demonstrate the application of public interest. Conclusion and Recommendations: To harmonize the principles of public interest in both frameworks, dialogue and cooperation between Islamic scholars and contemporary legal experts are essential. Education and awareness about the definition and application of public interest, along with developing adaptive legal and religious frameworks, can help address evolving societal needs while preserving core values.